Meeting Report: First Cardiovascular Outcomes Research in Perioperative Medicine Conference. (1st November 2022) - Bartels, Karsten; Howard-Quijano, Kimberly; Prin, Meghan; Shaefi, Shahzad; Steppan, Jochen; Sun, Eric C.; Williams, Brittney; Fox, Amanda A.; Namuyonga, Judith; Shaw, Andrew D.; Vavilala, Monica S.; Sessler, Daniel I.
Abstract : The first Cardiovascular Outcomes Research in Perioperative Medicine (COR-PM) conference took place on May 13, 2022, in Palm Springs, CA, and online. Here, we: (1) summarize the background, objective, and aims of the COR-PM meeting; (2) describe the conduct of the meeting; and (3) outline future directions for scientific meetings aimed at fostering high-quality clinical research in the broader perioperative medicine community.